System Usability Scale (SUS) Untuk Pengujian Usability Pada Pijar Career Center - M Yusuf; Yuli Astuti (Computer Engineering Departement, Universitas Komputer Indonesia, 2020)
PT Pijar Inovasi Nusantara is a company that creates the Pijar Career Center application. The incandescent career center application was created to meet the needs of the BKK Vocational School in distributing job vacancy information. In improving application user satisfaction, it is necessary to know the extent of usability in the Career Center application, it is necessary to use the usability test. This usability test uses the System Usability Testing (SUS) method that provides adequate results based on consideration of the small sample size, time and cost. The results of the SUS calculation will provide application information that is made feasible or not feasible to be applied. The value obtained for the application made is 79, the value will provide information that the incandescent career center application is appropriate to use.